Agglomeration and Economic Development: Import Substitution vs. Trade Liberalisation. - Puga, D; Venables, A (1999)
This paper analyzes a model of economic development in which international differences in industrial structure and income are caused by the agglomeration of industry in a subset of countries. Economic development may not be a gradual process of convergence by all countries but instead involve countries moving sequentially from the group of poor countries to the group of rich countries. The role of trade policy in promoting industrialization is studied. While both import substitution and unilateral trade liberalization may be successful in attracting industry, they attract different sectors and welfare levels are higher under trade liberalization.